PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL MEDIASI: Survei Pada Konsumen McDonald’s Di Surakarta - Fahmi Dina Maulani; Defa Mahkomah Putri; Fatika Fitri Nur Hidayah; Marjam Desma Rahadhini (Lembaga Pengembangan Kinerja Dosen, 2025)
This research report titled The Influence of Brand Image and Price on Purchase Decisions through Purchase Intention as a Mediating Variabel (Survey on McDonald’s Consumers in Surakarta). Aims to analyze the impact of brand image and price on consumers purchase McDonald’s products in Surakarta. The research untilized a quantitative descriptive method, collection data through questionnaires distributed to 40 respondents. The findings indicate that brand image does to not significantly influence purchasing decisions, whili price has a positive and signicant effect on purchase intention. Furthermore, purchase intention positively and significantly affects purchasing decisions. This research contributes to the understanding of consumer behavior in the fast-food industry, particulary in the context of McDonald’s.